Facts and fictions about polymorphism. (24th September 2015) - Cruz-Cabeza, Aurora J.; Reutzel-Edens, Susan M.; Bernstein, Joel
Abstract : We present new facts and correct old fictions about polymorphism in molecular crystals. Abstract : We present new facts about polymorphism based on (i) crystallographic data from the Cambridge Structural Database (CSD, a database built over 50 years of community effort), (ii) 229 solid form screens conducted at Hoffmann-La Roche and Eli Lilly and Company over the course of 8+ and 15+ years respectively and (iii) a dataset of 446 polymorphic crystals with energies and properties computed with modern DFT-d methods. We found that molecular flexibility or size has no correlation with the ability of a compound to be polymorphic. Chiral molecules, however, were found to be less prone to polymorphism than their achiral counterparts and compounds able to hydrogen bond exhibit only a slightly higher propensity to polymorphism than those which do not. Whilst the energy difference between polymorphs is usually less than 1 kcal mol −1, conformational polymorphs are capable of differing by larger values (up to 2.5 kcal mol −1 in our dataset). As overall statistics, we found that one in three compounds in the CSD are polymorphic whilst at least one in two compounds from the Roche and Lilly set display polymorphism with a higher estimate of up to three in four when compounds are screened intensively. Whilst the statistics provide some guidance of expectations, each compound constitutes a new challenge and prediction and realization of targeted polymorphism still remains a holy grail of materials sciences.